Contributions of Repertoires of Collective Actions in the Organization of the Populations Affected by Dams: A Study of the Itapebi Hydroelectric Power Plant - Oliveira Alves, Venícios; Gracinda Carvalho Teixeira, Maria (Organizações & Sociedade, 2021)
This research seeks to analyze the contributions of repertoires of collective actions in the organization of those affected by dams based on a study of the Itapebi Hydroelectric Power Plant. The repertoires of collective actions in this article are inspired by the author Charles Tilly and originate from the field of the theory of political sociology of social movements, defined as a set of forms of action in which there is political motivation. The initial assumption of the research is that the repertoires of collective actions created at the local level play a crucial role in the organization of those affected by the hydroelectric plant under study and help sustain the national demands of the Movement of Those Affected by Dams. The results of the research indicate that, through local experience, lived over the years by those involved, these repertoires have performed not only a central function in the organization of those affected in relation to compensatory issues proposals by the company responsible for the Itapebi enterprise, but also in the creation and strengthening public policies that will absorb local demands and their articulation with the national movement of the those by dams.